Heat transfer inside the rough-walled tubular channels of power plant elements - Kuznetsov, V. V.; Кузнецов, В. В. (My University, 2018)
Tubular channels with rough walls are now widely used for the formation of heat transfer surfaces of heat exchangers, which must meet the technical and economic requirements for power plants. Among these requirements, intensity and compactness are the main ones. The implementation of these requirements is possible with the intensification of heat transfer processes in a confined space. As shown by prior studies, the intensification of heat transfer on rough surfaces is based on a complex analysis of the effect of roughness in geometric parameters and thermophysical properties of heat agents on their efficiency. At the same time, the results of these studies are limited to the investigated heat agents, as well as the relative roughness heights. To compare the results of experimental studies on heat transfer, a generalized mathematical expression is derived on the basis of the Lion equation. It is intended for determining the heat transfer coefficient of rough surfaces taking into account the influence of velocity distribution on temperature drop in the turbulent core of the flow and the dependence of thickness of the viscous sublayer on the flow mode. The height is determined as the key factor of roughness. Surface roughness is divided into technical and regular. Comparison of the obtained solution to the available experimental data on heat transfer in technically rough pipes showed a difference in the results up to 10%, while in pipes with a regular roughness the divergence did not exceed 14%.
Тепловіддача всередені трубчастих каналів з шорсткою стінкою елементів енергетичних установок
Kuznetsov, V. V. Heat transfer inside the rough-walled tubular channels of power plant elements = Тепловіддача всередені трубчастих каналів з шорсткою стінкою елементів енергетичних установок / V. V. Kuznetsov // Shipbuilding & Marine Infrastructure. – 2018. – № 1 (9). – P. 92–99.
Keywords: roughness; tube; channel; intensification; heat transfer; шорсткість; труба; канал; інтенсифікація; тепловіддача